2007
DOI: 10.1016/j.vaccine.2007.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Development and preclinical evaluation of an alphavirus replicon vaccine for influenza

Abstract: We used a propagation-defective, single-cycle, alphavirus replicon vector system to produce viruslike replicon particles (VRP) expressing the hemagglutinin (HA) and neuraminidase (NA) proteins from influenza A/Wyoming/03/2003 (H3N2). Efficient production methods were scaled to produce pilot lots of HA VRP and NA VRP and clinical lots of HA VRP. HA VRP-induced high-titered antibody responses in mice, rabbits and rhesus macaques, as measured by ELISA or hemagglutination inhibition (HI) assays, and robust cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…on May 9, 2018 by guest http://jvi.asm.org/ sal challenge (13,19,20,27,34,35), and, in this study, we have shown that the i.d. route is also effective.…”
Section: Vol 84 2010 Chimeric Alphavirus Measles Vaccine Protects Msupporting
confidence: 65%
“…on May 9, 2018 by guest http://jvi.asm.org/ sal challenge (13,19,20,27,34,35), and, in this study, we have shown that the i.d. route is also effective.…”
Section: Vol 84 2010 Chimeric Alphavirus Measles Vaccine Protects Msupporting
confidence: 65%
“…Other advantages of VRP are their tropism for, and maturation of (5), DCs, which could result in enhanced T cell activation. A number of preclinical studies have reported that VRP induce potent immunity despite the presence of neutralizing antibodies (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Placement of an alternative gene(s) encoding an immunogen at the site of the deleted structural proteins results in its expression in lieu of the viral structural proteins (25,27). Alphavirus replicons have been used successfully to express immunogens for a number of pathogens (28)(29)(30)(31)(32)(33)(34). We report here efforts to develop a combination vaccine that would protect against all three encephalitic alphaviruses (VEEV, WEEV, and EEEV).…”
mentioning
confidence: 99%